A Test of Two Methods of Recall for Violent Events - Roberts, Jennifer (Journal of quantitative criminology, 2005)
This project took advantage of an opportunity to test the comparability of two different methods for collecting self-reports of violent incidents. Using a life events calendar (LEC) approach, we collected data from individuals about violent incidents that occurred within a 1–3-year prior time period. These individuals had been research participants in a previous study that collected information about violent incidents using prospective, weekly interviews. Results using the LEC method were compared with the weekly self-reports of violence for an overlapping recall period. This allowed us to see how well the recall of violent incidents at a later date mapped onto reports obtained within seven days of any incidents. Overall results show a significant amount of under-reporting using the life-event calendar methodology compared to the weekly interview approach, but some higher concordance of reporting was found for serious rather than minor violence.